The Optical Property of Mn- Doped ZnS Nanoparticles Synthesized by a Co-precipitation Method - Van, Bui Hong; Ben, Pham Van; Nhat, Hoang Nam; Thi, Tran Minh (Communications in Physics, 2012)
By a co-precipitation method, we have synthesized Mn-doped ZnS  nanoparticles with the Mn contents of 2-12 mol%from solutions Zn(CH3COO)2 0.1M, Mn(CH3COO)2 0.1M and Na2S 0.1M. XRD patterns, TEM images show these nanoparticles possess cubic crystalline structure with average size about of 3-4 nm. Photoluminescence spectra of samples present a broad yellow-orange band of 603 nm, its intensity increases with the increasing of Mn content from 2 mol%  to 8 mol % when the excitation power density increases from 0.06 W/cm2 to 0.21 W/cm2. However, while the intensity increases with the increasing of Mn content its position is almost unchanged. This band is attributed to the radiativetransition of electron in 3d5unfulfilled shell of Mn2+ ions [4T1(4G)→ 6A1(6S). The absorption spectra show main bands at 308-328 nm with strong intensity related to absorption near band edge of ZnS crystal. These bands related to Mn2+ absorption also appeared with weaker intensity. The photoluminescence excitation spectra monitored at the yellow-orange band  exhibited a band at 354 nm with strong intensity and  bands at 432, 466, 497 nm with weaker intensity.The band of 354 nm is attributed to the absorption near band edge. Simultaneously, the  bands of 432, 466, 497 nm are attributed to the absorption transitions of electrons from ground state 6A1(6S) to excited states 4T2(4D), 4A1(4G) - 4E(4G), 4T2(4G) of Mn2+ions in ZnS crystal, respectively.